We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
19
1
avatar

let f(x)=x^2-7x+12 and g(x)=x^2-9

what is (f/g)(x)?

x-4/x+3 where x ≠ -3,3

 

x+3/x-4 where x ≠ 3,4

 

x-4/x-3  where x ≠ -3,4

 

x+4/ x-3  where x ≠ -3,3

 Apr 10, 2019
 #1
avatar+99580 
+1

f(x)  =  x^2 - 7x + 12.......factor as (x -3) ( x - 4)

g(x)  = x^2 - 9....factor as  ( x -3) ( x + 3)

 

So

 

(f / g) (x)   =   f(x) / g( x)   =     (x - 3) ( x - 4 )             x - 4

                                              ___________  _=      ______   where x ≠ -3,3

                                               ( x - 3) ( x + 3)            x + 3

 

 

cool cool cool

 Apr 10, 2019

7 Online Users